Nano-Platelets as an Oxygen Regulator for Augmenting Starvation Therapy Against Hypoxic Tumor - Huang, Chunyu; Zhu, Chang; Chen, Jie; Huang, Kaibin; Li, Fang; Ding, Shunkai; Xia, Ligang; Jiang, Wei; Li, Yang (Frontiers in Bioengineering and Biotechnology, 2020)
The restriction of a tumor’s energy supply is proven to be an effective means of treatment. Glucose oxidase (GOx), an enzyme that catalyzes the conversion of glucose to glucolactone, producing oxygen and hydrogen peroxide in the process, has proved useful in this regard. However, hypoxia, which is implicated in tumor growth, has been found to mediate resistance to this type of tumor starvation. Here, we describe the design and testing of a platelet membrane mimetic, PMS, consisting of mesoporous silica nanoparticles (MSNs) loaded with metformin (MET) as an inner layer and platelet membranes (PM) as an outer layer that inhibits oxygen consumption by the tumor cells’ respiratory pathways and enhances the effectiveness of GOx. MET directly inhibits the activity of complex I in mitochondrial electron transport and is thus a potent inhibitor of cell respiration. PMS target tumor tissue effectively and, once internalized, MET can inhibit respiration. When oxygen is plentiful, GOx promotes glucose consumption, allowing amplification of its effects on tumor starvation. This combination of respiratory suppression by PMS and starvation therapy by GOx has been found to be effective in both targeting tumors and inhibiting their growth. It is hoped that this strategy will shed light on the development of next-generation tumor starvation treatments.